2009
DOI: 10.2147/ceg.s4512
|View full text |Cite
|
Sign up to set email alerts
|

The impact of biologics on health-related quality of life in patients with inflammatory bowel disease

Abstract: Background:Inflammatory bowel disease (IBD) is characterized by a chronic relapsing inflammation of the gastrointestinal tract. Adult IBD patients suffer from a disabling disease which greatly affects health-related quality of life (HRQoL). A worse HRQoL in these patients may result in a defensive and ineffective use of medical attention and thus higher medical costs. Because of its chronic nature, IBD may also cause psychological problems in many patients which may also influence HRQoL and care-seeking behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 62 publications
1
49
4
1
Order By: Relevance
“…Previously it was shown that optimal management of disease activity, stress, and coping is effective to reduce fatigue [13,[81][82][83][84]. Despite that [60].…”
Section: Discussionmentioning
confidence: 99%
“…Previously it was shown that optimal management of disease activity, stress, and coping is effective to reduce fatigue [13,[81][82][83][84]. Despite that [60].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Retrospective and nonrandomised studies have demonstrated IFX and ADA to have similar clinical outcomes in avoidance of corticosteroids, surgery, hospitalisation and improvement in quality of life in patients with CD. [13][14][15][16][17] In summary, biologic and retrospective clinical data suggest similar therapeutic activity of these agents in CD. Head-to-head direct comparative efficacy trials among anti-TNF agents for CD have not been performed.…”
Section: Introductionmentioning
confidence: 89%
“…9,10 In 2008, the Food and Drug Administration (FDA) approved two self-injectable biologics (adalimumab and certolizumab pegol) for treatment of moderate to severe Crohn's disease. Recently, in 2012, the FDA approved vedolizumab for a similar indication.…”
Section: Introductionmentioning
confidence: 99%